Theoretical Review: Adiabatic Coupler Engineering and Modification in Supporting SDGs 9 Efficient Optic Technology Engineering and Innovation - Rahmatta Thoriq Lintangesukmanjaya; Akhmad Iswardani; Binar Kurnia Prahani; Dwikoranto Dwikoranto; Noval Maleakhi Hulu (Journal of Current Studies in SDGs, 2025)
Objective: This study aims to describe the application of adiabatic coupler modification in efficient optical coupler engineering and to emphasize its contribution to the achievement of SDG 9 (Industry, Innovation, and Infrastructure). Method: The method used is a literature study through a review of relevant articles and Python software-based analysis to evaluate the impact of coupler modifications, as an effort to strengthen theoretical findings.  Results:  The results of this study show that the invariance principle-based reverse engineering approach is practical in designing directional couplers on waveguides. Combined with perturbation analysis of the coupled mode equations, this method produces directional couplers that are highly robust to parameter variations such as coupling coefficient and wavelength. However, changes in scale or resonance through Python integration do not significantly affect the apparent deviation of the coupler wave, so the efficiency of the coupler is mainly determined by the coupling coefficient and wavelength variations. Novelty: This study highlights the novelty of utilizing the invariance principle and resonance modification as an efficient and straightforward approach for adiabatic coupler optimization. Furthermore, the results demonstrate the significant contribution of adiabatic couplers to SDG 9 through their support for the development of sustainable optical communication infrastructure, increased energy efficiency, and innovation in next-generation optical technologies.